Efek hipokolesterolemik yogurt yang disuplementasi probiotik indigenous pada tikus sprague dawley=Hypocholesterolemic Effect of Yoghurt which Supplemented wtth Indigenous Probiotic Culture in Sprague Dawley Rats - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
A high serum cholesterol level might be a contributing risk factor for development of atherosclerosis and caused some degenerative diseases such as coronary heart disease. Therefore, maintaining serum cholesterol concentration at the normal level could reduce the risk of coronary heart disease. Some of probiotics and its products such as yoghurt could decrease serum cholesterol level. However, a variation was found among strains in their capability to decrease the cholesterol level. The purpose of this research was to study the ability of Lactobacillus sp Dadl3 and yoghurt which supplemented with Lactobacillus sp Dadl3 to reduce serum cholesterol level. Twenty four male Sprague Dawley rats, 2 month old, were divided into four groups of six rats each and fed with standard AIN-93 diet. For 2 wks before the experiments, rats were fed with standard diet (1 wk) and hypercholesterol diet (1 wk). At the end of the week, lipid profile were measured. When experiments started, standard diet were assigned to four groups of six and treated with 10% sterile skimmed milk, Lactobacillus sp Dadl3 culture, yoghurt, and yoghurt which supplemented with Lactobacillus sp Dadl3 culture 1 ml each. The treatments were given by force feeding. The results showed that total cholesterol, high density lipoprotein (HDL), triglyceride (TG), low density lipoprotein (LDL), and LDL/HDL ratio decreased significantly (P